Minimum quality standards and novelty requirements in a one-short development race - Jacek Prokop; Pierre Regibeau; Katharine Rockett (Economics: The Open-Access, Open-Assessment E-Journal, 2010)
We examine the timing and quality of product introduction in an R&D stopping game, where we allow for horizontal and vertical differentiation in the product market. We observe that discontinuous changes in introduction dates can occur as firms' abilities as researchers change. Further, when the research abilities of the firms differ, either the high ability firm or the low ability firm may be the first mover. The underlying research abilities of the firms determine the social optimality of the entry patterns we observe. Minimum quality standards and novelty requirements can play a role in correcting these suboptimal patterns of entry. While minimum quality standards increase welfare for a large range of research abilities, we find that increasing the novelty requirement does not necessarily increase either the profits or, consequently, the research investment incentives of the initial innovator, contrary to much of the cumulative innovation literature. Indeed, as the effect of policy interventions differs significantly across industries where quality improvement is steep and those where it is flat, targeted policies towards specific industries as are often observed in minimum quality standards are generally preferable to more broad-based policies.
Keywords: L15; L16; O31; O33; O34; 330; Innovation; minimum quality standards; novelty requirements; stopping game; Industrielle Forschung; Produktqualität; Normung; Suchtheorie; Innovationswettbewerb; Spieltheorie; Theorie